Grounding and the Myth of Ontological Innocence. Issue 2 (3rd April 2021) - Barker, Jonathan
ABSTRACT: According to the Ontological Innocence Thesis (OIT), grounded entities are ontologically innocent relative to their full grounds. I argue that OIT entails a contradiction, and therefore must be discarded. My argument turns on the notion of 'groundmates', two or more numerically distinct entities that share at least one of their full grounds. I argue that, if OIT is true, then it is both the case that there are groundmates and that there are no groundmates. Therefore, I conclude, OIT is false. Moreover, in seeing why OIT is false, we will be left with three heterodox options about grounding and reality's structure. So this paper's second conclusion is that, even after we have discarded OIT, we are in for an additional surprise.